AKSIOLOGI SPIRITUALITAS DALAM KONSELING - Gudnanto, Gudnanto; Pravesti, Cindy Asli; Wahyuni, Fitri; Kiswantoro, Arista (Universitas Muria Kudus, 2017)
Human beings are the highest in rank than other god creatures. Why is that?, of course the answer is because human beings have been given by the intellect and mind that can make men appear as a vicegerent on earth. Every human being has a belief in something that is considered supreme or sovereign. Confidence is what is called spiritual. Axiology is the branch of philosophy that studies the nature of value. Based on its main staple axiology can be divided into Ethics (philosophy of good bad human behavior) or moral philosophy and aesthetics or philosophy of magnificence. Many people feel has reached a goal or reach the pinnacle of success both career and matter, but felt something